Interplay between Intravitreal RvD1 and Local Endogenous Sirtuin-1 in the Protection from Endotoxin-Induced Uveitis in Rats. (9th June 2015) - Rossi, S.; Di Filippo, C.; Gesualdo, C.; Testa, F.; Trotta, M. C.; Maisto, R.; Ferraro, B.; Ferraraccio, F.; Accardo, M.; Simonelli, F.; D'Amico, M.
Abstract : Rat endotoxin-induced uveitis (EIU) is a well-established model of human uveitis. In this model, intravitreal injection of resolvin D1 (RvD1, 10–100–1000 ng/kg) 1 hour after subcutaneous treatment of Sprague-Dawley rats with lipopolysaccharide (LPS, 200  μ g/rat) significantly prevented the development of uveitis into the eye. RvD1 dose-dependently increased the expression of sirtuin-1 (SIRT1) within the eye, while it decreased the expression of acetyl-p53 and acetyl-FOXO1. These effects were accompanied by local downregulation of some microRNAs related to the expression and activity of SIRT1. These were miR-195-5p, miR-200a-3p, miR-34a-5p, and miR-145-5p. An increase of manganese superoxide dismutase and decrease of caspase 3 were evident after RvD1 treatment. In another set of experiments, the protective effects of RvD1 (1000 ng/kg) were partly abolished by the pretreatment of the rats with EX527 (10 mg/kg/day, i.p.), a specific inhibitor of SIRT1 activity, for 7 days prior to the induction of EIU in rats. Similarly, the effects of RvD1 (1000 ng/kg) on the SIRT1 protein expression were abolished by Boc2, N - t -butoxycarbonyl-PLPLP, a specific formyl-peptide receptor type 2/lipoxin A receptor antagonist. Therefore, an interplay of the SIRT1 activity on the RvD1 mediated resolution of EIU is argued.